Kaempferia galanga L.: Progresses in Phytochemistry, Pharmacology, Toxicology and Ethnomedicinal Uses - Wang, Si-Yu; Zhao, Hui; Xu, Hong-Tao; Han, Xiao-Dong; Wu, Yun-Shan; Xu, Fang-Fang; Yang, Xiao-Bo; Göransson, Ulf; Liu, Bo (Frontiers in Pharmacology, 2021)
K. galanga is an aromatic medicinal herb. It is locally to India and distributed in China, Myanmar, Indonesia, Malaysia, and Thailand. K. galanga is a Traditional Chinese Herb Medicine (TCHM), with the function of regulating qi-flowing and harmonizing stomach, digesting food and relieving pain. In addition, the rhizomes of it have been used widely as spices since its highly aromas. The aim of this review is to summarize the current progresses of the phytochemistry, ethnomedicinal uses, pharmacology and toxicology of K. galanga. All the data on K. galanga were based on different classical literary works, multiple electronic databases including SciFinder, Web of Science, PubMed, Science Direct, Wiley, Springer, CNKI, and PhD, MSc dissertations in Chinese and Pharmacopoeias prior to December 2020. We collected a total of 99 publications after preliminary screening, among them, 24 publications used for traditional uses, 34 publications used for phytochemistry, 39 publications used for pharmacological activities. The results showed that 97 compounds have been isolated and identified from the rhizome of K. galanga, including terpenoids, phenolics, cyclic dipeptides, flavonoids, diarylheptanoids, fatty acids and esters. Modern pharmacology studies have shown that the extracts or secondary metabolites of the herb possessed various bio-activities. Anti-inflammatory, anti-oxidant, anti-tumorous, anti-bacterial, and anti-angiogenesis, which were closely related to its abundant ethnomedicinal uses. In conclusion, K. galanga is a valuable medicinal herb which is used traditionally in various countries and regions of the world, including India, China, Malaysia, Indonesia and Thailand for the treatment of a wide variety of ailments. A number of constituents isolated from the rhizomes of K. galanga exhibit various pharmacological activities. This review is expected to provide insights for future research of new drugs based on extracts and bioactive compounds from K. galanga.